The International Fund for Agricultural Development's 2021 Rural Development Report cites A4NH evidence in its analysis of opportunities for transforming food systems - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
The 2021 report draws on research funded by A4NH on food system transformation and promising consumer- and food-environment- oriented policy options to include in the food systems transformation agenda in low- and middle income countries. It provides analysis to inform policies, programs and investments to promote inclusive food system transformation.